Overview of extension philosophies and methods - Davis, Kristin E.; Sulaiman, V. Rasheed (Global Forum for Rural Advisory Services, 2018)
Extension (also known as rural advisory services) has risen and fallen on the global development agenda. The focus on extension increased during the green revolution era. Today, due to factors such as food price crises and climate change, extension is increasingly recognised as critical for rural development. This note aims to introduce programme managers to extension philosophies and methods over the past decades. It demonstrates that each approach originated in specific circumstances, and has both merits and demerits. There are many philosophies and methods for extension, and views on what it is all about have changed over time. Extension originally was conceived as a service to ‘extend’ research-based knowledge to the rural sector to improve farmers’ lives. It includes components of technology transfer, rural development goals, and non-formal education. The traditional view of extension in developing countries was focused on increasing production, improving yields, training, and transferring technology. Today’s understanding of extension goes beyond technology transfer to facilitation; beyond training to education; and includes assisting farmer groups to form, dealing with marketing issues, and partnering with a broad range of service providers.